Saintifik Qs. Al-Fatihah Ayat 02 : Perspektif Tantawi Jauhari dalam Kitab Al-Jawahir fi Tafsir Al-Qur’an Al-Karim - Shonhaji Shonhaji; Agus Helmi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The Qur'an is the word of Allah SWT that discusses various types of knowledge, including science, hence the scientific values within the Qur'an exist, one of which is in Surah Al-Fatihah, verse 02. One interpretation of the Qur'an that discusses science is the work of Tantawi Jawhari, who has a different perspective in interpreting the Qur'an compared to most other scholars, making it a distinctive feature of scientific interpretation that is considered interesting. This interpretation utilizes images to provide understanding or viewpoints in offering explanations. This research employs a qualitative library research method, with the primary source being 'al-Jawahir fi Tafsir al-Qur'an al-Karim,' a work by Tantawi Jawhari. The results of this research indicate that Surah Al-Fatihah holds scientific perspectives in its entirety, one of which is illustrated in verse 02, explaining that there are many realms, including the upper and lower realms. The upper realm is filled with creatures such as aliens and other beings of Allah, while the lower realm consists of elements like the earth, oceans, and mountains, among which there are humans.